Catalytic Removal of Volatile Organic Compounds over Porous Catalysts - Xingtian Zhao; Shaohua Xie; Huanggen Yang; Jiguang Deng; Hongxing Dai (The Global Environmental Engineers, 2015)
In this review, we summarize the recent research progress on the preparation and catalytic performance of meso- and macroporous metal oxide or mixed metal oxide (including manganese oxides, cobalt oxides, iron oxides, chromium oxides, and perovskite-type oxides) catalysts and their supported transition metal and noble metal catalysts for the oxidative removal of typical volatile organic compounds (VOCs), which were prepared using the hard-templating and polyvinyl alcohol-protected reduction methods, respectively. Most of these porous catalysts performed well for the addressed reactions, which was associated with their surface areas, adsorbed oxygen species concentrations, low-temperature reducibility, interactions between noble metal or metal oxide and support as well as porous structures. In addition, the perspectives for developing high-performance catalytic materials and novel VOCs removal technologies are also proposed.